FT-IR and solid-state NMR investigation of phosphorus promoted hydrotreating catalyst precursors - Decanio, Elaine C.; Edwards, John C.; Scalzo, Thomas R.; Storm, David A.; Bruno, Joseph W. (Journal of catalysis, 1991)
The effect of phosphorus on the structure of NiMo/Al 2O 3 hydrotreating catalyst precursors has been investigated. Calcined and reduced P/Al 2O 3, PNi/Al 2O 3, P-Mo/Al 2O 3, and PNiMo/Al 2O 3 (where the wt% P = 0.0 to 10.0, wt% Mo = 8.0 to 12.0, and wt% Ni = 4.0) have been studied using FT-IR, XRD, and 31P and 27Al MAS NMR techniques. Phosphoric acid reacts with alumina hydroxyls forming monomeric and polymeric phosphates. At the higher phosphorus loadings, aluminum phosphate is also formed. On calcined PNi/Al 2O 3, nickel phosphate is formed. This leads to a decrease in density of NO sites in the reduced state as measured by CO adsorption. The addition of up to 1.5 wt% P to Mo(8)/Al 2O 3 promotes the formation of octahedral molybdena on the alumina surface. However, the addition of > 2.0 wt% P results in the formation of bulk M003 and Al 2(MoO 4) 3 in both PMo(8)/Al 2O 3 and PMo(12)/Al 2O 3. CO adsorption on reduced PNi(4)Mo(8)/Al 2O 3 samples shows that the presence of 0.5 wt% P causes a significant increase in the number of sites adsorbing CO. Increasing the P loading further causes a decrease in the number of adsorbing sites; this decrease can be attributed to the formation of either nickel phosphate or nickel molybdate.